2022
DOI: 10.3390/ijms23147640
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Erythrocytes from Gaucher Patients Induces Phenotypic Modifications in Macrophages, Driving Them toward Gaucher Cells

Abstract: Gaucher disease (GD) is caused by glucocerebrosidase deficiency leading to the accumulation of sphingolipids in macrophages named “Gaucher’s Cells”. These cells are characterized by deregulated expression of cell surface markers, abnormal secretion of inflammatory cytokines, and iron sequestration. These cells are known to infiltrate tissues resulting in hematological manifestations, splenomegaly, and bone diseases. We have already demonstrated that Gaucher red blood cells exhibit altered properties suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Of note, patients who suffer from lysosomal storage disorder, Gaucher disease, show iron deposits in the splenic macrophages ( Clarke et al, 2021 ; Lefebvre et al, 2018 ). Iron sequestration in Gaucher macrophages was attributed to the hepcidin-mediated downregulation of ferroportin, or more recently to increased erythrophagocytosis of Gaucher RBCs ( Dupuis et al, 2022 ). Based on our study, it is plausible that defects in proteostasis, due to defective lysosomal-mediated protein quality control, may contribute to aberrant iron management in Gaucher macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, patients who suffer from lysosomal storage disorder, Gaucher disease, show iron deposits in the splenic macrophages ( Clarke et al, 2021 ; Lefebvre et al, 2018 ). Iron sequestration in Gaucher macrophages was attributed to the hepcidin-mediated downregulation of ferroportin, or more recently to increased erythrophagocytosis of Gaucher RBCs ( Dupuis et al, 2022 ). Based on our study, it is plausible that defects in proteostasis, due to defective lysosomal-mediated protein quality control, may contribute to aberrant iron management in Gaucher macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…However, iron alone is not sufficient for triggering ferroptosis and inflammation. Recent reports indicated that erythrocyte lipid peroxides, sphingosine and erythrocyte-bound mitochondrial DNA render erythrophagocytosis pro-inflammatory 23,42,43 . In the past, we have shown that erythrocytes of MAFLD patients contain increased sphingosine 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, various mechanisms driving erythrophagocytosis have also emerged. Reduced CD47 surface levels, binding of TSP-1 on conformationally changed CD47 [16], and sphingolipid-induced reduction of deformability [10] can result in erythrophagocytosis. We recently showed that erythrocytes of these patients also exhibit increased sphingosine levels [8].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, they showed that the exposed phosphatidylserine of erythrocyte membranes in NASH is partially responsible for erythrophagocytosis. Our previous results have shown that erythrocyte membranes of NASH patients also exhibit reduced levels of sphingomyelin [7] and accumulation of sphingosine [8], which can both result in phosphatidylserine exposure [9,10]. However, erythrocyte phosphatidylserine exposure can also be triggered by reduced nitric oxide levels [11].…”
Section: Introductionmentioning
confidence: 98%